Rainfall Infiltration in Unsaturated Soil Slope Failure - Wu, Lizhou; Zhou, Jianting (SpringerBriefs in Applied Sciences and Technology, 2023)
This is an open access book. The aim of this book is to provide a thorough grounding in rainfall-induced landslides from three aspects: the coupling effect of hydraulic and mechanic; the analytical, numerical, and physical simulation methods, and the controlling factors underlying the problem of rainfall-induced landslides. The improved numerical methods, nonlinear, and linear iterative methods which can be used to address the related unsaturated infiltration problems are also presented. This book is an essential reading for researchers and graduate students who are interested in rainfall infiltration, landslides, slope stability, and geohazards in fields of civil engineering, engineering geology, and earth science. The book is written to guide professional engineers and practitioners in slope engineering and geohazard management. This book can enhance their understanding of rainfall-induced landslides, help them analyze a specific problem, prevent landslides, and design engineering slopes according to the local soil and climate conditions.